Dietary Habits, Anthropometric Values, and Microvascular Reactivity in Older Persons of Both Sexes Living at Retirement Home in Osijek, Croatia - Drenjančević I; Prošić I; Firi L; Stupin A; Jukić I (Clinical Interventions in Aging, 2025)
Ines Drenjančević,* Ivan Prošić,* Lucija Firi, Ana Stupin, Ivana Juki&#x0107Department of Physiology and Immunology, Faculty of Medicine Osijek, Osijek, Croatia*These authors contributed equally to this workCorrespondence: Ines Drenjančević, Department of Physiology and Immunology, Faculty of Medicine Osijek, J. Huttlera 4, Osijek, 31000, Croatia, Tel +385912241406, Email ines.drenjancevic@mefos.hrPurpose: To examine the correlation between dietary habits, anthropometric measurements, and microvascular reactivity with respect to sex in older adults (aged > 65 years) residing in organized accommodation within retirement homes.Patients and Methods: Sixty-nine older persons who live in a retirement home in Osijek, Croatia volunteered to participate (34 men and 35 women) in this observational cross-sectional study. Study was performed in the period from May 1, 2024 to July 1, 2024. Subjects weight, height, waist circumference, hip circumference, blood pressure and heart rate were measured, and body mass index (BMI) and waist to hip ratio (WHR) were calculated. To assess microvascular endothelium-dependent vasodilation, skin microvascular post-occlusion reactive hyperemia (PORH) was assessed by Laser Doppler Flowmetry. Long-term dietary patterns and dietary habits were evaluated with validated EPIC-Norfolk food frequency questionnaire, in Croatian language. Study was approved by Ethical Committee of Faculty of Medicine Osijek (Class: 641-01/24-01/04, No: 2158-61-46-24-86).Results: Mean age (standard deviation, SD) of 34 older men was 83.8 (5.4) years, and of 34 older women 83.6 (5.5) years. The mean BMI of all subjects was 27.1 kg/m2 classifying them as overweight. Both men (WHR 0.99 (0.07)) and women (WHR 0.90 (0.06) had significantly higher than normal WHR (normal WHR, men < 0.90, women < 0.80), suggesting the visceral type of obesity. The mean intake of NaCl was higher (NaCl g/day men 6.91 (1.43), women 6.93 (2.51)), and intake of vitamin D lower (vitamin D μg/day men 3.64 (1.35), women 3.47 (2.61)) than recommended values (NaCl g/day < 5 g/day, vitamin D 15 μg/day). Men consumed significantly more alcohol (alcohol g/day men 1.48 (3.36) vs women 0.17 (0.39), P = 0.03), while women had higher carotene intake (β-carotene, μg/day men 2603 (1020) vs women 3478 (1580), P = 0.009). Microvascular reactivity was similar in women and men (PORH, R-O% men 85.2 (30.6) vs women 76.2 (31.5), P > 0.05). However, women had a significant negative correlation of waist circumference (R = − 0.350, P =0.04) and WHR (R = − 0.406, P = 0.02) to PORH.Conclusion: Dietary habits were similar between older men and women, except for higher alcohol intake in men and higher carotene intake in women. In older women, microvascular reactivity was negatively associated with waist circumference and WHR, underscoring central obesity as a key cardiovascular risk factor in this population. Given the increased cardiometabolic vulnerability in postmenopausal women, measures of central adiposity should be routinely monitored in geriatric care.Keywords: older persons, food frequency questionnaire, sex differences, microcirculation, post-occlusive reactive hyperemia